Genetic variability and heritability of seed yield and yield contributing characters in safflower (Carthamus tinctorius L.): Genetic variability and heritability of seed yield and yield contributing characters in safflower (Carthamus tinctorius L.) - V N WANI; L N TAGAD; MUKTA MANE (Journal of Oilseeds Research, 2023)
In the present study, genotypic and phenotypic variability were worked out on 34 genotypes of safflower for yield and yield contributing characters at Department of Genetics and Plant breeding at Sam Higginbottom University of Agriculture, Technology, and Sciences in Prayagraj during rabi 2021. The experiment was conducted by using RBD design with three replications. The information was compiled using 12 characters to examine the genotypes of safflower with regard to genetic variability, heritability, the connection of yield contributing components with yield The highest percentage of PCV (64.93 ), GCV (65.26) and heritability (99% ) were found for number of Capitulum per plant. Low heritability estimates were found for the seed index and capitulum diameter whereas moderate genetic gain was seen for capitulum diameter, days to maturity, days to 50% flowering, and plant height. When a trait is highly heritable and genetic progress as a percentage of the mean, it is likely that additive gene action, with equal contributions from non-additive and additive gene action, is responsible for the trait.